Literature review Plate Heat Exchanger - Emil Mahfuzi (BKS-TM Indonesia, 2025)
Plate heat exchangers (PHEs) are indispensable devices in numerous industrial applications due to their high heat transfer efficiency, compact design, and operational flexibility. This article provides a comprehensive review of advancements in PHE technology, drawing upon recent research to consolidate current knowledge and identify future research directions. The review employs a thematic approach, categorizing research into key areas: plate geometry and configuration, fluid flow distribution and pressure drop characteristics, analytical and numerical modeling and simulation techniques, design optimization methodologies, the application of nanofluids and other advanced working fluids, and innovations in materials and configurations. A critical review of selected influential articles is also presented, highlighting their specific contributions and methodologies. The discussion reveals that continued advancements in plate design, sophisticated modeling tools like CFD, and the exploration of novel fluids such as nanofluids are significantly enhancing PHE performance. However, challenges persist, particularly in accurately modeling two-phase flows, mitigating fouling, and developing advanced materials. Future research directions include the integration of additive manufacturing for complex geometries, the implementation of smart and adaptive control systems, and a greater emphasis on lifecycle sustainability. This review underscores the pivotal role of PHEs in driving energy efficiency and sustainability across various industrial sectors.